2021
DOI: 10.3390/diagnostics11071134
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of sICAM-1 and sVCAM-1 Levels in the Cerebrospinal Fluid of Patients with Schizophrenia Spectrum Disorders

Abstract: Immunological explanatory approaches are becoming increasingly important in schizophrenia research. In this context, the function of the blood-brain barrier (BBB) and the blood-cerebrospinal fluid (CSF) barrier (BCSFB) plays an essential role. Different adhesion molecules, such as intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1), are key elements in sustaining the integrity of the BBB and BCSFB. The objectives of this study were to (1) compare the levels of different ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
(102 reference statements)
2
14
0
Order By: Relevance
“…A meta-analysis indicated BBB leak in SZ, reflected by higher levels of CSF albumin [33 ▪▪ ]. Three subsequent studies corroborated this result and indicated BBB leakage across a relatively similar percentage of the patients (15.8% [52 ▪▪ ], 19% [53 ▪▪ ], 15% [34 ▪▪ ]). Reductions in the tight junction protein CLDN5 were reported in the hippocampus [43 ▪▪ ] and serum of the patients [42].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…A meta-analysis indicated BBB leak in SZ, reflected by higher levels of CSF albumin [33 ▪▪ ]. Three subsequent studies corroborated this result and indicated BBB leakage across a relatively similar percentage of the patients (15.8% [52 ▪▪ ], 19% [53 ▪▪ ], 15% [34 ▪▪ ]). Reductions in the tight junction protein CLDN5 were reported in the hippocampus [43 ▪▪ ] and serum of the patients [42].…”
Section: Discussionmentioning
confidence: 85%
“…In SZ, CSF sICAM1 was also higher than reference control levels. Levels of these proteins were similar among first-episode and chronic SZ patients, suggesting that alterations were not a consequence of a degenerative process, nor of cumulative antipsychotic use [34 ▪▪ ]. Elevated serum levels of PAI-1 and other pro-inflammatory cytokines were also reported in another study with large samples, and levels were even higher in SZ patients that had experienced Acute Ischemic Stroke (SZ-AIS) (150 SZ, 150 SZ-AIS, and 150 controls) [59].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Different from the CSF which is characterize by CD4 + central memory T cells [ 122 , 123 ], the choroid plexus contains CD4 + effector memory T cells localized within the epithelium near to MHCII cells and with a pattern of receptors (TCR) peculiar and specific to CNS antigens [ 19 , 124 ].…”
Section: The Immunoregulatory Function Of the Choroid Plexusmentioning
confidence: 99%